Proposição de um modelo de melhoria no processo de pregão eletrônico - Ribeiro, Eduardo Martins (2021)
Carrying out an economically viable public procurement process that, as a source, adds value as activities of public servants, in order to meet the interests of society, remains a major challenge for the Public Administration. Despite the innovations made in the bidding laws, the operational routine of prioritizing the procedural formalism in acquisitions is present in the bodies, causing inefficiency and harming contracting. Exploring other concepts, such as the strategic management of supplies in the private area and bringing it to the public sector can reduce the waste of public spending and improve acquisitions through electronic trading in these times of economic instability aggravated by COVID-19. Based on the definitions of IN 05/2017-MPOG, this research divides the purchasing process into three stages: planning, supplier selection and contract management. Thus, with this established structure, the aim is to integrate the PDCA management cycle, formed by the phases of planning, execution, control and corrective actions with the stages of the procurement process. Thus, this research aims to propose the implementation of a cyclical management to improve processes in public tenders as a learning process. A qualitative research was carried out, applying the action-research method. The sources used were the researcher's participatory research in the purchasing process, feedback from the actors involved in the process, documentary, and bibliographic survey. As a result, it was found that the continuous improvement practices adopted increased the index of items accepted in the supplier selection stage and the conformity of materials received by the applicant, resulting in a reduction in rework and better budget execution by the Public Institution in the case studied. The main contribution that this work presents is an approach that can generate greater efficiency in planning with the use of the cyclical management model in public procurement processes available throughout the public administration environment.